2010
DOI: 10.1002/bit.22689
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic gene expression regulation model for growth and penicillin production in Penicillium chrysogenum

Abstract: As is often the case for microbial product formation, the penicillin production rate of Penicillium chrysogenum has been observed to be a function of the growth rate of the organism. The relation between the biomass specific rate of penicillin formation (q(p)) and growth rate (mu) has been measured under steady state conditions in carbon limited chemostats resulting in a steady state q(p)(mu) relation. Direct application of such a relation to predict the rate of product formation during dynamic conditions, as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 29 publications
2
36
0
Order By: Relevance
“…3), indicating that the industrial process may accelerate the high expression of IPN acyltransferase. Enzyme activity assays strongly indicated that isopenicillin-N synthase (IPNS) was the main rate-limiting enzyme for penicillin G biosynthesis [25]. Herein, we explored the dynamic changes in the intracellular proteomes associated with penicillin production of P. chrysogenum during the pilot and the industrial conditions.…”
Section: Discussionmentioning
confidence: 99%
“…3), indicating that the industrial process may accelerate the high expression of IPN acyltransferase. Enzyme activity assays strongly indicated that isopenicillin-N synthase (IPNS) was the main rate-limiting enzyme for penicillin G biosynthesis [25]. Herein, we explored the dynamic changes in the intracellular proteomes associated with penicillin production of P. chrysogenum during the pilot and the industrial conditions.…”
Section: Discussionmentioning
confidence: 99%
“…10,22 Several groups have described that transcription of the genes encoding for the enzymes in the penicillin biosynthesis pathway is repressed by glucose. 9,[23][24][25] In P. chrysogenum, penicillin biosynthesis is repressed by glucose preventing expression of the pcbAB, pcbC and penDE genes. 25 According to published results, glucose induced not only higher rates of respiration but also greater energy production than lactose as carbon source in P. chrysogenum NRRL 1915 strain.…”
Section: Discussionmentioning
confidence: 99%
“…In other words, the expression level of pcbAB and penDE does not seem to be a relevant factor for antibiotic biosynthesis. Douma et al 24 reported that the control of penicillin biosynthesis is exerted by a single rate-limiting enzyme: the isopenicillin N synthase encoded by the pcbC gene. Meanwhile, other groups report that the rate limiting step reside either at ÎŽ-(L-α-aminoadipyl)-L-cysteinyl-D-valine synthetase or at isopenicillin N synthase.…”
Section: Discussionmentioning
confidence: 99%
“…The enzymatic products of xylC (benzaldehyde dehydrogenase), xylM and xylA (xylene monooxygenase), and xylB (benzyl alcohol dehydrogenase) are involved in the oxidation of aromatic effectors to the corresponding benzyl alcohol, benzaldehyde, and benzoate respectively (Van Dien and de Lorenzo, 2003). Furthermore, it is widely accepted that control of the enzyme level on the flux of a pathway is distributed between all participating enzymes (Douma et al, 2010). Nevertheless, these enzymes do not exert the same level of control on the flux of the pathway, which is usually dominated by a single ratelimiting enzyme.…”
Section: Pu Promotermentioning
confidence: 99%
“…The current state of the art is rather limited to the recent work of Douma et al (2010) presenting the development of a simple dynamic gene regulation model to describe biomass and penicillin production in a chemostat. It was shown that although the gene regulation model was only validated using enzyme activity assays instead of measuring mRNA levels, it nevertheless improved significantly the prediction of the bioprocess demonstrating the benefits of accounting for genetic events in biochemical engineering.…”
Section: Introductionmentioning
confidence: 99%